Curcumol alleviates liver fibrosis by inducing endoplasmic reticulum stress-mediated necroptosis of hepatic stellate cells through Sirt1/NICD pathway - Sun, Sumin; Huan, Sheng; Li, Zhanghao; Yao, Yue; Su, Ying; Xia, Siwei; Wang, Shijun; Xu, Xuefen; Shao, Jiangjuan; Zhang, Zili; Zhang, Feng; Fu, Jinbo; et al. (PeerJ, 2022)
Liver fibrosis is a repair response process after chronic liver injury. During this process, activated hepatic stellate cells (HSCs) will migrate to the injury site and secrete extracellular matrix (ECM) to produce fibrous scars. Clearing activated HSCs may be a major strategy for the treatment of liver fibrosis. Curcumol isolated from plants of the genus Curcuma can effectively induce apoptosis of many cancer cells, but whether it can clear activated HSCs remains to be clarified. In the present study, we found that the effect of curcumol in treating liver fibrosis was to clear activated HSCs by inducing necroptosis of HSCs. Receptor-interacting protein kinase 3 (RIP3) silencing could impair necroptosis induced by curcumol. Interestingly, endoplasmic reticulum (ER) stress-induced cellular dysfunction was associated with curcumol-induced cell death. The ER stress inhibitor 4-PBA prevented curcumol-induced ER stress and necroptosis. We proved that ER stress regulated curcumol-induced necroptosis in HSCs via Sirtuin-1(Sirt1)/Notch signaling pathway. Sirt1-mediated deacetylation of the intracellular domain of Notch (NICD) led to degradation of NICD, thereby inhibiting Notch signalling pathway to alleviate liver fibrosis. Specific knockdown of Sirt1 by HSCs in male ICR mice further exacerbated CCl4-induced liver fibrosis. Overall, our study elucidates the anti-fibrotic effect of curcumol and reveals the underlying mechanism between ER stress and necroptosis.
Keywords: Curcumol; Necroptosis; ER stress; Sirt1; NICD; Liver fibrosis